Introduction: Balkan Romance Within the Balkan Sprachbund - Virginia Hill; Adam Ledgeway (Languages)
This article provides a short introduction to Balkan Romance, examining and exemplifying a number of its principal features. In particular, the discussion begins in §2 with a review of the main morphosyntactic features of the four principal sub-branches of Old Romanian spoken today within the Balkan Sprachbund (Daco-Romanian, Aromanian, Istro-Romanian, and Megleno-Aromanian), tracing the treatment of such Balkanisms both in the traditional philological literature (§3) and their more recent formalization and expansion in the theoretical literature dedicated to the Balkan Sprachbund (§4). This is followed in §5 by a discussion of some of the dialects spoken in southern Italy and their key morphosyntactic features. These varieties, although not situated in the Balkan Sprachbund proper, have nonetheless either developed under contact with Balkan languages, as in the case of the Romance dialects of the extreme south of Italy which have been in centuries-long contact with Greek (§5.1), or, in the case of Italo-Albanian, have evolved under contact with local Italo-Romance varieties (§5.2). The discussion concludes in §6 with an overview of the principal issues discussed in each of the contributions.